MECHANIZATION OF BELGIAN GLASS ENTERPRISES IN KOSTYANTYNIVKA DURING THE PERIOD OF INDUSTRIAL BOOM (1909–1914) (Південний архів (історичні науки), 2025)
The purpose of the work is to investigate the processes of mechanization of the Belgian glass enterprises of Kostyantynivka during the general industrial boom of 1909–1914. These are enterprises near the Kostyantynivka station (modern Kostyantynivka, Donetsk region), which belonged to joint-stock companies: glass factories (Societe des Verreries de Donetz); mirror factories (Societe anonyme des Glaceries du midi de la Russie). The main products are mirrors, bottles and sheet glass. It is important to note that this is the only similar complex of Belgian glass enterprises not only in the Donetsk region and the Dnieper region, but also in Ukraine as a whole. Belgian manufacturers occupied leading positions in the new period of development of these enterprises. The general economic situation combined the existing opportunities with new goals and tasks of industrialists. Theoretical developments will allow to detail the specifics of mechanization processes. Methods. The methodological basis of the work is the general scientific principles of historicism, objectivity and scientific reliability. Special-historical methods were used: historical-systematic, comparative-historical. Results. The study examines the processes of mechanization of Belgian glass enterprises in Kostyantynivka during the general industrial boom of 1909–1914. The issue of attracting Belgian capital to the glass industry of Ukraine has further developed. Conclusions. The achievements of advanced industrial countries, primarily Belgium itself, in the mechanization of glass production attracted the attention of Belgian owners of glass factories in Kostyantynivka. In the wake of the new industrial boom, these glass enterprises are experiencing a certain increase in production capacity and technical power. During this period, new machines and more powerful power equipment are partially introduced. However, the basis of glass and bottle production, as before, remained manual labor. Mirror production stood out favorably, significantly mechanized, with the widespread use of machines and machines powered by electricity. A somewhat similar situation is observed at glass factories in Belgium itself.
Keywords: machine, glass, mirror, bottle, electricity, industry, Belgium, Ukraine